Imaging and outcome correlates of ctDNA methylation markers in prostate cancer: a comparative, cross-sectional [68Ga]Ga-PSMA-11 PET/CT study - Kluge, Kilian; Lotz, Vincent; Einspieler, Holger; Haberl, David; Spielvogel, Clemens; Amereller, Dominik; Kramer, Gero; Grubmüller, Bernhard; Shariat, Shahrokh; Haug, Alexander; Hacker, Marcus; Kenner, Lukas; et al. (Clinical epigenetics, 2025)
BACKGROUND: To validate the clinical utility of a previously identified circulating tumor DNA methylation marker (meth-ctDNA) panel for disease detection and survival outcomes, meth-ctDNA markers were compared to PSA levels and PSMA PET/CT findings in men with different stages of prostate cancer (PCa). METHODS: 122 PCa patients who underwent [68Ga]Ga-PSMA-11 PET/CT and plasma sampling (03/2019-08/2021) were analyzed. cfDNA was extracted, and a panel of 8 individual meth-ctDNA markers was queried. PET scans were qualitatively and quantitatively assessed. PSA and meth-ctDNA markers were compared to PET findings, and their relative prognostic value was evaluated. RESULTS: PSA discriminated best between negative and tumor-indicative PET scans in all (AUC 0.77) and hormone-sensitive (hsPC) patients (0.737). In castration-resistant PCa (CRPC), the meth-ctDNA marker KLF8 performed best (AUC 0.824). CHST11 differentiated best between non- and metastatic scans (AUC 0.705) overall, KLF8 best in hsPC and CRPC (AUC 0.662, 0.85). Several meth-ctDNA markers correlated low to moderate with the tumor volume in all (5/8) and CRPC patients (6/8), while PSA levels correlated moderately to strongly with the tumor volume in all groups (all p < 0.001). CRPC overall survival was independently associated with LDAH and PSA (p = 0.0168, p < 0.001). CONCLUSION: The studied meth-ctDNA markers are promising for the minimally-invasive detection and prognostication of CRPC but do not allow for clinical characterization of hsPC. Prospective studies are warranted for their use in therapy response and outcome prediction in CRPC and potential incremental value for PCa monitoring in PSA-low settings.
Keywords: Circulating Tumor DNA; Prostatic Neoplasms; Gallium Isotopes; nádory prostaty; Prostatic Neoplasms, Castration-Resistant; Humans; izotopy gallia; lidé středního věku; Biomarkers, Tumor; Aged; Prostate-Specific Antigen; senioři; lidé; PET/CT; cirkulující nádorová DNA; nádorové biomarkery; nádory prostaty rezistentní na kastraci; DNA Methylation; metylace DNA; Edetic Acid; Male; Middle Aged; Positron Emission Tomography Computed Tomography; prostatický specifický antigen; prognóza; Aged, 80 and over; Cross-Sectional Studies; senioři nad 80 let; radioizotopy galia; Gallium Radioisotopes; mužské pohlaví; EDTA; průřezové studie; Prognosis